Public Policy and Wheat Market in Pakistan (The Pakistan Development Review, 1986)
Drawing upon a series of country-wide surveys undertaken in 1986, the study addresses the micro and macro policy issues related to the operations of the wheat market in Pakistan. It focuses on the relative roles of the private traders and the government in determining the prices received by the primary producers and the final consumers of wheat. It finds that the government occupies the "commanding heights" in the wheat market. To regulate the market it employs, as policy instruments, voluntary procurement, storage and transportation of wheat, milling of, wheat into flour, and supplying wheat and flour to the consumers through both ration shops and the open market. The study recommends that while the scope of private traders' activities needs to be widened, the government must continue to operate effectively and more selectively. In particular, the present policy of the voluntary procurement of wheat should be used, though at a reduced level, to stabilize farmers' income, and a (restructured) rationing system must function to subsidize the consumption of wheat and wheat flour by the poorer section of the society.